2020
DOI: 10.1177/1178646920910159
|View full text |Cite
|
Sign up to set email alerts
|

The 4 D’s of Pellagra and Progress

Abstract: Nicotinamide homeostasis is a candidate common denominator to explain smooth transitions, whether demographic, epidemiological or economic. This ‘NAD world’, dependent on hydrogen-based energy, is not widely recognised as it is neither measured nor viewed from a sufficiently multi-genomic or historical perspective. Reviewing the importance of meat and nicotinamide balances during our co-evolution, recent history suggests that populations only modernise and age well with low fertility on a suitably balanced die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 287 publications
(350 reference statements)
0
8
0
Order By: Relevance
“…Pellagra may be endemic in the millions in poverty who are meat and milk deprived masquerading as Kwashiorkor ("juvenile pellagra") or "environmental enteropathy" or as poor cognition or general ill-health and susceptibility to adverse effects of infection or trauma. A community screening test that would not be difficult to develop should be a priority and where found family and other contacts should be traced as they will be at risk [38][39][40].…”
Section: Test and Tracementioning
confidence: 99%
See 1 more Smart Citation
“…Pellagra may be endemic in the millions in poverty who are meat and milk deprived masquerading as Kwashiorkor ("juvenile pellagra") or "environmental enteropathy" or as poor cognition or general ill-health and susceptibility to adverse effects of infection or trauma. A community screening test that would not be difficult to develop should be a priority and where found family and other contacts should be traced as they will be at risk [38][39][40].…”
Section: Test and Tracementioning
confidence: 99%
“…The global South was also unlucky in its meat supply particularly in Africa where a lack of animal domesticates and an abundance of human and veterinary infections in the tsetse fly belt such as trypanosomiasis and rinderpest and were prone to pellagra. Darker skin colour reduces the diagnostic help from the sunburn of pellagra but is a mixed blessing if it is acting as a warning (including allowing self-treatment), of the more serious cognitive effects of nicotinamide deficiency [38].…”
Section: Poverty Inequality and Discriminationmentioning
confidence: 99%
“…An iconic example of a nutritional trap is when a low meat intake risks the degenerative condition pellagra whose sufferers, with inferior cognitive and social intelligence, were ostracised as the "Butterfly caste", and contracted infections such as tuberculosis (TB) also closely linked with poverty [8,9]. Terms used to stigmatize, shame, blame and pillory pellagrins are still in common usage today to keep the poor in their place.…”
Section: Extreme Meat Inequality: the Forgotten Case Of Pellagramentioning
confidence: 99%
“…Furthermore, previous work in our group demonstrated that 20 mM nicotinamide induced cytotoxic effects on stem cell-derived cultures within 3 days of application [ 7 ], whereas these cultures responded positively to supplementation with nicotinamide within a dose range of 5 to 10 mM in vitro [ 18 ], implying that vitamin levels need to be tightly controlled to maintain normal neuronal functioning. On the contrary, Pellagra is nutritional disorder caused by a severe tryptophan/niacin deficiency which leads to a range of symptoms including dermatitis, diarrhoea, dementia and depression, also common in Parkinsonism [ 16 , 32 ]. In other neurological disorders, alterations in nicotinamide have also been implicated in Alzheimer’s disease and Huntington’s disease (reviewed in [ 33 ]).…”
Section: Introductionmentioning
confidence: 99%